Urdu Poem: Meaning, Phases and Trends - Dr Tariq Mahmood Hashmi (بازیافت, 2017)
Urdu poem has different phases in its developmental process. There was no any concept of thematic poem in classical age of Urdu poetry but Nazeer Akbar Abadi is an exception who wrote poems on themes. Modern Urdu poem is started in colonial period of India. Muhammad Husain Azad, Hali and some other poets wrote thematic poems from the platform of Anjuman-e-Punjab. Progressive poets wrote poems on social and economical issues.On the other hand poets who were affiliated with Halqa Arbab-e-Zoq focused on inner feelings and individuality of man. Movement of new poetry started after 1960. Poets who were affiliated with new poetry movement raised some philosophical questions about man and new issues of modern society